Vom Hymnus zum Gebet Gattungs- und Gebrauchswechsel liturgischer Lieder in Mittelalter und Früher Neuzeit - Kulagina, Pavlina; Lallinger, Franziska (Liturgie und Volkssprache, 2022)
This volume brings together studies on the diverse ways that the genres and usage of hymns and sequences transformed in the middle ages and early modern period, taking them from being Latin liturgies to becoming vernacular meditations.